(untitled) (Law, State and Telecommunications Review, 2021)
Purpose - The purpose of this paper is to analyze in theory and practice the extent and ways the role of regulators in collaborative regulatory systems differs from their roles in more traditional, state-led regulatory systems. Methodology/Approach/Design - The descriptive and analytical methodology of this paper is supported by primary and secondary sources of research data: books, newspapers, official documentation, independent reports, and private stakeholders’ analysis. Moreover, field experiences of eminent professionals and senior civil servants have also been taken into consideration to reach conclusions and provide useful information. Findings - Main finding is that the regulator in collaborative systems acts as a facilitator or mediator, one who traces and deploys the regulatory activity inside a network of participation, and less as the wielder of state-authority. Practical implications - The analysis in this paper can be of considerable use to all actors who deploy regulatory activity in order to deliver better regulatory outcomes to society, performing newer and different techniques, assessing the collaborative regulator’s role in practical cases. Originality/Value - This paper analyzes the role of the collaborative regulator by addressing the differences and similarities between collaborative regulation and an array of regulatory styles and approaches.